Dougie Young and political resistance in early Aboriginal country music. Issue 3 (October 2019) - Martin, Toby
Abstract: Country music has a reputation for being the music of the American white working-class South and being closely aligned with conservative politics. However, country music has also been played by non-white minorities and has been a vivid way of expressing progressive political views. In the hands of the Indigenous peoples of Australia, country music has often given voice to a form of life-writing that critiques colonial power. The songs of Dougie Young, dating from the late 1950s, provide one of the earliest and most expressive examples of this use of country music. Young's songs were a type of social-realist satire and to be fully understood should be placed within the broader socio-political context of 1950s and 1960s Australia. Young's legacy was also important for Aboriginal musicians in the 1990s and the accompanying reassessment of Australia's colonial past. Country music has provided particular opportunities for minority and Indigenous groups seeking to use popular culture to tell their stories. This use of country music provides a new dimension to more conventional understandings of its political role.